Ayn Rand papers - Rand, Ayn.; Rand, Ayn.; Rand, Ayn.; Rand, Ayn.; Rand, Ayn.; Rand, Ayn.; Rand, Ayn
Chiefly holograph and typewritten drafts, galleys, and proofs of Rand's novels We the Living (1936), Anthem (1938), The Fountainhead (1943), and Atlas Shrugged (1957). Addition includes holograph essays on subjects such as Watergate, the Supreme Court, economics, and inflation written by Rand between 1971 and 1974 for her newsletter, The Ayn Rand Letter. Also includes other material pertaining to the newsletter and to The Objectivist and photographs.
Partial microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Author and philosopher. Born 1905; died 1982.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Supreme Court; Economics; Inflation (Finance); Objectivism (Philosophy); Watergate Affair, 1972-1974.; Authors; Philosophers